Empowering the residents of Aptrans Batujajar in training in dairy and meat product to support business independence - Putri Widyanti Harlina; Edy Subroto; Rossi Indiarto; Fetriyuna Fetriyuna (Universitas Muhammadiyah Magelang, 2024)
Milk and meat are animal food sources that are rich in important nutrients for the health of the human body. However, because they are included in the perishable foods category, these two food ingredients are vulnerable to contamination and damage. Therefore, further processing is needed to increase the nutritional value and extend the shelf life of processed products. This community service program aims to transfer knowledge and skills in processing milk (yogurt) and meat (sausages) to partner communities, namely the residents of Aptrans Batujajar. Through training and mentoring, the main goal is to increase public awareness and creativity in processing dairy and meat foods. The method used in this program involves hands-on training in the manufacture of dairy and meat products. Additionally, assistance and monitoring are carried out to ensure in-depth understanding and increase community creativity in utilizing the knowledge gained. Through this program, a new product of economic value was successfully created, namely yogurt. This product has the potential to be further developed as an independent business that can support entrepreneurial creativity in the community.